The predictors of osteoporosis preventive behaviors in women based on health belief model - Ali Khani Jeihooni; Alireza Hidarnia; Mohammad hossein Kaveh; Ebrahim Hajizadeh (Gonabad University of Medical Sciences, 2017)
Osteoporosis, as a disease, is characterized by low bone mass and micro architectural deterioration of bone tissue. The aim of this study was to survey the predictors of osteoporosis preventive behaviors based on health belief model. This cross-sectional study was carried out on 401 randomly selected women referring to health centers. Data collection was based on health belief model. The employed instrument was confirmed by a panel of experts. Content validity ratio, content validity index, face validity, and exploratory factor analysis were used to determine the validity of the tool. Test-retest internal consistency was employed to determine the reliability. The mean age of women was 40.9±6.2 years. The variables of perceived susceptibility, motivation for walking behavior and variable of perceived sensitivity for nutrition behavior were predicted. The walking performance had a significant association with perceived susceptibility and motivation, the nutritional performance had a significant positive association with perceived susceptibility and self-efficacy and a negative correlation with perceived barriers. The variables under study explained 29.1% of the variance in walking behavior and 20.2% of the variance in nutrition behavior in osteoporosis prevention. This study indicated health belief model is capable to predict nutrition and walking behaviors for the prevention of osteoporosis. Hence, this model can be used as a framework for designing and implementing educational interventions for the prevention of osteoporosis in women.